An Analysis on Mixed English-Indonesian Demonstration Banners on Instagram - Min Adlina; Eddy Setia; T. Thyrhaya Zein (CSR International Journal, 2021)
Indonesia is currently experiencing a significant heated political upheaval as many students from various universities took to the streets to express their dissatisfaction with the House of Representatives (DPR). This research was more focused on identifying the type of sarcasm in the demonstration banner against the criminal code bill that were occurred in 2019 as the movement of the sea of Indonesian students in voicing opinions and forms of harsh criticism to the government policies that are considered detrimental to the people. The research used qualitative method. The data used in this research were 48 demonstration banners against the Criminal Code Bill on the Instagram account. The results showed that propositional sarcasm was obtained as much 10 data (21%), lexical sarcasm was 11 data (23%), illocutionary sarcasm was 26 data (54%) with sentimental contradiction (18 data), manner violation (1 data), lexical contradiction (3 data), and hyperbolic combination (3 data), while ‘like’ prefixed sarcasm was 1 data (2%) from 48 sarcasm in the demonstration banner against the criminal code bill. This research could also be a reference material for the researchers who want to research the topics that were relevant to this research. For the readers, it was expected to understand and take lessons from the result of research for application in social life.